Short-channel effects in tunnel field-effect transistors with different configurations of abrupt and graded Si/SiGe heterojunctions - Nguyễn, Đăng Chiến (2023)
The heterojunction technique has recently been considered as an effective approach to simultaneously achieve a high on-current and low ambipolar off-leakage in tunnel field-effect transistors (TFETs). In this paper, we propose the various configurations of abrupt and graded Si/SiGe heterojunctions for TFETs and investigate their short-channel effects by using two-dimensional simulations. It is shown that the semiconductor bandgap has to be properly considered together with the drain-induced barrier thinning in studying short-channel effects because scaling down the bandgap considerably deteriorates short-channel effects in TFETs. Among the basic configurations of Si/SiGe heterojunctions, the slantingly graded Si/SiGe heterostructure is most excellent in optimizing the electrical characteristics of the extremely scaled TFETs without short-channel effects. The slantingly graded Si/SiGe TFET with superior short-channel performance exhibits a potential device for low power and high packaging density integrated circuits.